Improving the Performance Characteristics of Three‐Phase Asynchronous Induction Motor Drive Using Hybrid Systems Control Method Based on Direct Torque Control - Shafiee-Fini, Mohammad; Navardi, Mohammad Javad; Ghasvari, Hossein (Journal of control science and engineering, 2025)
In this study, a hybrid control method based on direct torque control (DTC) was introduced to enhance the performance features of the three‐phase asynchronous induction motor drive. Model‐based predictive control methods are among the types of control methods used for hybrid systems. In the suggested method, the concepts of flux and torque vector orientation were utilized to decrease the impacts of flux and torque ripples in a multiobjective cost function. Subsequently, the optimal voltage vector was chosen according to the minimization of the intended objective function by applying the predictive control concepts. In this technique, the selection of the optimal vector is more guaranteed compared to the DTC method in accordance with the table since the objective function is assessed in every control cycle and the optimal voltage vector is chosen accordingly. In addition, the implementation of the suggested control method is easily possible. Based on the results of the simulation, the presented control method outperformed the classical torque direct control and predictive torque control (PTC) method in the flux and torque fluctuation results.